Lettuce seedlings quality: The effects of white and blue light exposure - Luković Kristina; Adžić Slađan; Zečević Veselinka; Đurić Nenad; Perišić Vladimir; Gavrilović Bojana; Rakonjac Aleksandra (Selekcija i Semenarstvo)
In the Balkans, the production of globally cultivated green leaf lettuce (Lactuca sativa L.) can be slow due to reduced quality and intensity of solar insolation. Our research aimed to investigate the effects of artificial illumination and the duration of light exposure on the growth and quality of two lettuce genotypes seedlings: Genesis and Jukebox. The research was conducted at the Institute for Vegetable Crops Smederevska Palanka, Serbia. Lettuce seeds were sown in 9 styrofoam containers per genotype, filled with commercial substrate. In the phase of three leaves, plants were placed in plant growth chambers under multispectral white (W) LEDs and monochromatic blue (B) LEDs (three containers per LED and genotype), while three containers were kept in the greenhouse and served as control. The plants were cultured in plant growth chambers for 25 days under a 9h/15h and 10h/14h (light/dark) photoperiod, to simulate outdoor conditions. Morphological growth parameters (number of leaves and plant weight) were measured on the 11th and 25th days. Chlorophyll content was measured on the 4th, 11th, 18th and 25th days. Plants grown under W and B LEDs had a significantly higher number of leaves, plant weight, and chlorophyll content than plants grown in a greenhouse. Using energy-efficient white and blue LED lights in lettuce seedling production during 18-25 days positively impacts seedling quality, and with this seedling production, the plants can achieve high yields and quality.